Mutation Analysis of 63 Northwest Chinese Probands with Oculocutaneous Albinism. (2nd January 2021) - Chuan, Zhang; Yan, Yousheng; Hao, Shengju; Zhang, Qinghua; Zhou, Bingbo; Feng, Xuan; Wang, Xing; Liu, Furong; Zheng, Lei; Cao, Zongfu; Ma, Xu
ABSTRACT: Purpose: To identify the mutational spectrum of 63 northwest Chinese probands with Oculocutaneous albinism (OCA), and identify correlations between phenotype and genotype. Methods: We recruited 63 clinically diagnosed with OCA patients in Gansu Provincial Maternal and Child Health Care Hospital. Mutation screening analysis was performed by direct sequencing and NGS-target sequencing to screen the variants on genes related to OCA. PolyPhen2 and PROVEN tools were used to predict the possible functional role of the novel variants. We assessed the pathogenicity of the novel mutations according to the clinical interpretation of genetic variants by ACMG/AMP 2015 guideline. Results: By molecular testing, 56 of the OCA probands were diagnosed as OCA 1, three were OCA 2 and one was OCA 4. The most common variants of TYR were c.929insC(33.7%), c.896 G > A(12.5%), c.832 C > T(9.6%).We found five novel variants of TYR that have not previously been reported. Conclusions: We make an accurate diagnosis and classification for the OCA probands. Our result enlarged the mutational spectrum of TYR and SLC45A2 . These findings could be useful for genetic counseling and gene diagnosis of OCA in Northwest of China.